Cyanide adsorption from cassava wastewater onto calcined periwinkle shell - Nnanna Chimaobim Eke-emezie; Benjamin Rueben Etuk (Brawijaya University, 2019)
Local cassava processing industries produce large quantities of wastewater containing cyanide which is toxic in nature with negative impacts on the environment when disposed without treatment. In this study calcined periwinkle shell (CPS) was prepared, characterized and used to adsorb cyanide present in cassava wastewater. Equilibrium studies were conducted in batch set ups to investigate the influence of process variables such as adsorbent dosage, pH, temperature, contact time and initial cyanide concentration on the adsorption process. The highest removal rate of cyanide from cassava wastewater was found to be 78.34% with equilibrium reached at fixed adsorbent dosage of 3.0 g at contact time of 80 minutes. Cyanide adsorption was also observed to be dependent on pH with the maximum adsorption of cyanide occurring at a pH 10. The percentage of cyanide removed decreased with increase in cyanide concentration. Results from the study confirm calcined periwinkle shell as low cost and effective adsorbent which can be used for the removal of cyanide from cassava wastewater